The Modified Relay Race Games in Enhancing Gross Motor Skills of Children Aged 5-6 Years at TK Negeri 01 Sungai Rumbai - Yulianti, Siska; Siska , Widia; Andre, Lesis; Sari, Ayu Mustika (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This thesis is motivated by the underdevelopment of children's gross motor skills and the limited variety of games that can stimulate gross motor skills in 5-6 year old children at Sungai Rumbai State Kindergarten 01. The purpose of this study was to determine the stimulation of children's gross motor skills through modified relay race games.This research is descriptive and uses qualitative methods. The data sources were two classroom teachers and 15 students aged 5-6. Data collection techniques included observation, interviews, and documentation. Data analysis techniques included data reduction, data presentation, and conclusions. Data validity techniques included data triangulation.The results of the research on the forms of relay race modification games at TK Negeri 01 Sungai Rumbai include balloon relay, colored ball relay and rubber pass relay. The steps of the relay race modification game include, preparing the tools and materials to be used, dividing the children's teams according to the number of children, the teacher exemplifies the game to the children, guides the children to take positions, the teacher gives the signal to start the game, guides the first and second players to pass objects, guides the third player to put objects into the container at the finish line and guides the game until it is finished. The gross motor skills of children aged 5-6 years at TK Negeri 01 Sungai Rumbai through the relay race modification game are proven to increase from the category of starting to develop (MB) to developing very well (BSB). Before being implemented, 73% of children were in the category of starting to develop (MB) and after being implemented, 80% of children were in the category of developing very well (BSB). The balance indicator improved from the